Pertanggungjawaban Pidana Anak Sebagai Pelaku Tindak Pidana Kekerasan Seksual - Doddy Hermawan; Alpi Sahari; Ahmad Fauzi (Universitas Batanghari Jambi, 2021)
Crime against child perpetrators in Indonesia is getting more and more worrying from time to time. One of the most common crimes committed by children and their victims are children is sexual abuse. One of the triggers for the emergence of sexual abuse by children with child victims is the proliferation of pornographic sites on the internet that can be easily accessed by children via mobile phones or the internet due to technological advances. Technological progress has a positive impact because it makes it easier for humans to fulfill their needs but also has a negative impact if it is misused. The type of research used in this research is normative legal research. The main data in this study are secondary data, namely data or information from the review of similar research documents that have been done before, library materials such as books, literature, newspapers, magazines, journals or archives that are in accordance with the research to be discussed. The data analysis in this study was qualitative, which was based on the relevance of the data to the problem, not based on the amount of data (quantitative). Based on the results of research that in Law no. 23 of 2002 concerning Child Protection as amended by Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection also provides regulated child protection. Strictly speaking Article 15 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection states that: